Postoperative Outcomes After Robotic Liver Resection of Caudate Lobe: A Systematic Review - Gabriela Del Angel Millan; Gianluca Cassese; Fabio Giannone; Celeste Del Basso; Mariantonietta Alagia; Marco Lodin; Igor Monsellato; Marco Palucci; Federico Sangiuolo; Fabrizio Panaro (Medicina, 2024)
Background and Objectives: Resection of the caudate lobe of the liver is considered a highly challenging surgical procedure due to the deep anatomic location of this segment and the relationships with major vessels. There is no clear evidence about the safety and effectiveness of robotic resection of the caudate lobe. The aim of this systematic review was to report data about the safety, technical feasibility, and postoperative outcomes of robotic caudate lobectomy. Materials and Methods: A systematic review of the MEDLINE and SCOPUS databases was undertaken, including studies published until 19 December 2024. Results: A total of 5 studies including 110 patients were selected. Of these surgeries, 56.3% were performed for malignant tumors. Tumor size varied significantly between 0.9 and 7.7 cm in the largest diameter. The mean operative time was 184.5 min (range 70–522 min), and the estimated blood loss was 95.5 mL (range 10–1500 mL). The median hospital length of stay was 4.2 days (range 2–19 days) and no cases of conversion to open were reported. All the patients underwent R0 resection. In total, 24 out of 110 patients (21.8%) developed postoperative complications, with 1.8% of all patients developing a major complication (Clavien–Dindo classification ≥ III). No perioperative deaths were reported by the included studies. Conclusions: Few retrospective studies investigating the outcomes of robotic resection of the caudate lobe are currently available in the literature. From published data, it may be a safe and feasible alternative to open and laparoscopic caudate lobectomy in selected patients in referral HPB centers. Further studies with larger sample sizes are needed to confirm such preliminary findings.